Localization of myosin IC and myosin II in Acanthamoeba castellanii by indirect immunofluorescence and immunogold electron microscopy (The Rockefeller University Press, 1990)
Polyclonal antisera have been raised against purified Acanthamoeba myosin II and to a synthetic 26 amino acid peptide that corresponds in sequence to the phosphorylation site of Acanthamoeba myosin IC. These antisera are specific for their respective antigens as determined by immunoblotting after SDS-PAGE of total cell lysates. By using the antisera, localization studies were performed by indirect immunofluorescence and by immunogold electron microscopy. Myosin II occurred in the cell cytoplasm and appeared to be concentrated in the cortex. Immunogold cytochemistry revealed at high resolution that myosin II is organized into rodlike filaments approximately 200 nm long. The antibody raised against the myosin IC synthetic peptide recognized both the plasma membrane and the membrane of the contractile vacuole. The plasma membrane staining was labile to treatment with saponin suggesting an intimate association of the myosin IC with membrane phospholipids. Immunogold cytochemistry with the antimyosin IC synthetic peptide showed that the myosin IC is closely associated with the membrane bilayer.